Quality of life after microvascular mandibular reconstruction for osteoradionecrosis—A prospective study. Issue 7 (5th February 2019) - Danielsson, Daniel; Munck‐Wikland, Eva; Hagel, Eva; Halle, Martin
Abstract: Background: Reconstructive surgery for mandibular osteoradionecrosis is increasing; however, evidence regarding the impact on health‐related quality of life is lacking. The current exploratory study prospectively investigates whether resection with reconstruction is associated with changes in HRQoL parameters for these patients. Methods: Seventeen patients underwent microvascular reconstruction for mandibular osteoradionecrosis between 2012 and 2015, and 16 completed the EORTC quality of life questionnaires QLQ‐C30 and QLQ‐H&N35 1 month before and 1 year after surgery. Results: Increases in emotional ( P  = 0.01) and social functioning ( P  = 0.004) were observed, together with improvements in the fatigue ( P  = 0.04), appetite loss ( P  = 0.02) and pain ( P  = 0.02) scores, as evaluated by the QLQ‐C30. Pain reduction was further confirmed by the QLQ‐H&N35 ( P  = 0.04), which also showed improved scores for feeling ill ( P  = 0.001) and sexual difficulties ( P  = 0.04). Conclusion: This exploratory study suggests that microvascular reconstruction after mandibular osteoradionecrosis may improve HRQoL, with an emphasis on pain reduction; however, further studies are needed.